Evaluasi pembelajaran daring untuk mengurangi potensi kecurangan akademik: A case study - Angela Caroline; Yenny Sugiarti (Jurusan Akuntansi,Fakultas Bisnis dan Ekonomika,Universitas Surabaya, 2023)
The Covid-19 has had an impact on all fields, especially in education. Higher education changes its learning methods from face-to-face to distance learning. The teaching assistant class at PTS ”X” must also turn into distance learning. The online learning process has some limitations so that it increase the academic fraud by students. The purpose of this study is to explain the types of events that occur during online learning in the assistance class, the causal factors and efforts to prevent them. This research is a case study in the teaching assistant class at University X. The data was obtained by inteviewing, observing, and analyzing the assistance documents which were then analyzed by qualitative method. The results of this study indicate that online learning process at University X has not been effective to prevent academic fraud so plagiarism, data manipulation, cheating, and collusion occur. Some recommendations to improve the online learning system should be carried out, such as enforcement of rules and strong punishment related to fraud, modification of the assessment system, increased supervision and good communication between assistants and assistant class participants. The results of this study are expected to be adopted by universities to increase the effectiveness of the online learning system used.